Prevalence and outcomes of balloon undilatable chronic total occlusions: Insights from the PROGRESS-CTO. (1st September 2022) - Simsek, Bahadir; Kostantinis, Spyridon; Karacsonyi, Judit; Alaswad, Khaldoon; Karmpaliotis, Dimitri; Masoumi, Amirali; Jaffer, Farouc A.; Doshi, Darshan; Khatri, Jaikirshan; Poommipanit, Paul; Gorgulu, Sevket; Abi Rafeh, Nidal; et al.
Abstract: Background: The prevalence, treatment, and outcomes of balloon undilatable lesions encountered in chronic total occlusion (CTO) percutaneous coronary intervention (PCI) have received limited study. Methods: We examined the clinical characteristics and procedural outcomes of balloon undilatable lesions in the Prospective Global Registry for the Study of CTO Intervention (PROGRESS-CTO, NCT02061436). Results: Of 6535 CTO PCIs performed between 2012 and 2022, 558 (8.5%) lesions were balloon undilatable. In this subset, patients were older (mean age 67 ± 10 vs. 64 ± 10, p < 0.001) and had higher prevalence of comorbidities: diabetes mellitus (54% vs. 40%, p < 0.001), prior PCI (71% vs. 59%, p < 0.001), prior myocardial infarction (52% vs. 45%, p = 0.003), and prior coronary artery bypass graft surgery (44% vs. 25%, p < 0.001). The CTO lesion length was estimated to be 34 ± 23 mm, mean J-CTO score was 2.9 ± 1.1 and mean PROGRESS-CTO score was 1.4 ± 1.0. A cutting balloon was used in 27%, a scoring balloon in 15%, laser in 14%, rotational atherectomy in 28%, orbital atherectomy in 10%, intravascular lithotripsy in 1% and other modalities/approaches in 5%. Balloon undilatable lesions had lower technical success (90.9% vs. 93.8%, p = 0.007) and higher incidence of major adverse cardiovascular events (MACE) (composite of in-hospital death, acute myocardial infarction, stroke, re-PCI, emergency CABG, and pericardiocentesis) (5.0% versus 1.3%, p < 0.001). Conclusion: Approximately 1 in 12 CTO (8.5%) lesions are balloon undilatable. Treatment of balloon undilatable lesions is associated with lower technical success and higher in-hospital MACE. Highlights: Approximately 1/12 chronic total occlusion (8.5%) lesions are balloon undilatable Balloon undilatable lesions had lower technical success (90.9% vs. 93.8%, p = 0.007) Balloon undilatable lesions had higher MACE (5.0% versus 1.3%, p < 0.001)